Challenges in managing the isolated cervical lymphadenopathy in absence of thyroid nodule - Talwar, Nikhil; anand, Gautam; Jassi, Kayenaat Puran Singh; Dhamija, Rahul; Bhaskar, Sumit; Kumar, Akshay (International Surgery Journal, 2022)
Differentiated thyroid cancer make up the vast majority of thyroid cancers with papillary thyroid cancer representing 84% of all thyroid cancer diagnoses. Papillary carcinoma of the thyroid presenting primarily as lateral neck swelling is rare. In the absence of thyroid swelling further evaluation should be done to exclude the primary tumors of scalp and head and neck region. Diagnosis of this condition is made by ultrasound guided FNAC. Surgery is the main treatment modality of choice. Here, we reported a case of an adult female who presented with isolated cervical lymphadenopathy and FNAC revealed metastatic papillary carcinoma of thyroid. Total thyroidectomy with central and posterolateral cervical neck dissection was done, with histology confirming as papillary thyroid carcinoma with local lymphnode metastasis.